Effect of Heat-treatment on the Corrosion Resistance of AZ91 Coated with Aluminum Sputtering Film - Ryosuke Yoshita (Science Faculty of Chiang Mai University, 2019)
Magnesium alloys, which are lightest in the practical metals, have several superior characteristics such as dimensional stability and electromagnetic shielding. These characteristics would expect to be applied in many fields. While, magnesium alloys show low corrosion resistance. It is necessary to be improved it. In this study, we aim to improve the corrosion resistance of AZ91 with aluminum film by the sputtering deposition. Polarization curve measurement evaluated corrosion rate using the Tafel extrapolation method. SEM observation was carried out for surface observation of samples. Although corrosion resistance is not improved only by aluminum sputtering deposition due to defects in film, heat treatment for 3 hours at 553K after sputtering deposition improved corrosion resistance of the AZ91 alloy. In the case of heat treatment at 623K and 673K for 3 hrs, magnesium atoms diffused through the aluminum film and reached to the surface of the film. Consequently, the heat treatments at these temperatures degraded corrosion resistance of the films. One the other hand by the heat treatment at 553K, corrosion resistance of AZ91 coated with the aluminum film increased with increasing heat treatment time. Thus, optimization of heat treatment after sputtering is important to obtain high corrosion resistance of the AZ91 magnesium alloy in this method.